Synthesis and Crystal Structure of Diaquodiformatodi(4-methyl pyridine)copper(II) - Klaib, Sami (Asian Journal of Chemistry, 2014)
Ternary complex i.e., diaquodiformatodi(4-methyl pyridine)copper(II) has been prepared and the solid state structure was determined using X-Ray structure analysis. The molecule crystallizes in monoclinic space group P21/c with a = 9.6070 (5) Å, b = 11.5441 (5) Å, c = 7.7163 (5) Å, a = 90, b = 98.045 (4), g = 90, V = 847.348 A3. The structural data are consistent with the presence of Jahn-Teller distortion in the overall hexacoordinate octahedral geometry of the molecule. The crystal packing is through an extensive hydrogen bonding and ring-ring p-p interactions resulting in a supra molecular frame work.